An exploration of funding gap on capital projects in state universities: case of Midlands State University - Makaza, Ntombizodwa (Midlands State University, 2018)
The aim of the study is to evaluate the effect of the funding gap on capital projects in state universities. The researcher was mainly focusing on the situation at MSU. The researcher used mixed research methodology which involves qualitative and quantitative methods in data gathering. Research information was gathered using questionnaire and interviews. Results indicated that funding gap do exists in state universities especial those in developing countries. At Midlands State University it was discovered that the major cause of funding gap are government budget deficit and the unstable political environment that is prevailing in the country. It was also discovered because of funding gap the university is failing to complete its capital projects on time which has a repercussion effects on students accommodation and lecture rooms. Therefore the researcher is recommending the university to venture into public-private partnerships and also introduce building levy and sports levy.